The State and Society of China A Century Long Ensemble of "Great Power" and "New Citizens" - Gao, Yong (Social Development Experiences in China,, 2018)
This book places the topic of the state and society in the context of modern development in China over the past century, investigating the dynamic relation and internal tension between the state's power enhancement and society's vitality activation instead of simply regarding the country and society as two separate entities. Building a modern country and activating the people's vitality involves three closely linked and mutually supporting aspects: establishing the identity recognition of the people to unite the nation; adjusting the organizational system of the society to promote mobilization and institute a social incentive system; and determining dominant strategies and means for the interaction between the country and society to address social-governance issues. This book carefully sheds light on the logic behind China's roundabout strategy for building a modern country and motivating the vitality of its people.